On interpreting Lithuanian past tenses in major linguistic works on Lithuanian grammar - Paulauskienė, Aldona (Lietuvių kalba, 2010)
The verb in Lithuanian possesses two simple past tenses, i.e. the past simple and the past frequentative tense. Specialists of comparative historical grammar have not shown any greater interest in the past frequentative tense since it is only typical of Lithuanian. One of the reasons is that Latvian, the other surviving Baltic language, does not possess it; furthermore, in the past a large part of Lithuania did not employ the tense either. However, now it is widely used and all grammars consider the past simple and the past frequentative tense equally significant. Still the paradigm of simple tenses in Lithuanian has not been defined as yet, as the past frequentative tense has not been given theoretical evaluation in the framework of other simple tenses. The article covers the interpretation of past tenses in major grammars of Lithuanian (from the first volume dating back to 1653 to present-day Lithuanian grammars). The paradigmatic relations of past tenses as presented in the numerous sources as well as language facts helped identify the following main features: the role of the category of aspect in the process of the formation of the past frequentative tense, relations between the past frequentative and the past simple tense, and finally, the place of the past frequentative tense in the paradigm of Lithuanian simple tenses.
Keywords: none